Painted and photographed portraits in Finland 1839-1870 - Käyhkö, Unto (1995)
The subject covered in this research is portrait photography as art during the early days of photography in Finland 1839-1870. The scope of the study has been restricted to this period in order to achieve a uniform art historical perspective. The points of contact between portrait photography and art, the major photographers and the camera picture in the service of painting art are examined in the study. The thesis begins with a review of earlier research and the theoretical literature pertinent to the study approach. Using these as a basis, an attempt has been made to create a methodological system for the research that is based on hermeneutic theory. The studies on the hermeneutics of art history carried out by Gottfried Boehm and Oskar Bätschmann, who were especially influenced by the work of Hans-Georg Gadamer, have been of central importance in forming the perspective of this work. Early photography aspired for a likeness with portrait painting by borrowing the general positions and subject types widely used throughout the history of art. Photography and painting both exploited and influenced each other. Photography produced a credible likeness which was and still is the central problem, although a complex and contradictory one, of the portrait. Many painters used the camera picture as an aid in achieving a credible likeness or similarity with the subject. The portrait landscapes of M. von Wright and A.J. Desamod the Younger are presented as examples of the use of the picture projected by the camera obscura and daquerreotype camera. R.W. Ekman, E.J. Löfgren and A. Edelfelt used portrait photographs of the early period as an aid in their portraits. Of the three, Edelfelt is the main example of the dilemma and limited scope of likeness. A few of the leading early photographers are presented as examples of photographic artists. The 1840's are represented by A.J. Desamod the Younger and F. Rehnström, and the 1850's by P.C. Liebert, L.J. Peldan and F. Mebius. Examples of the carte-de-visite photographers of the 1860's include C.P. Mazer, A.C.E. Chiewitz, J.J. Reinberg and C.A. Hårdh. According to my research, the portrait in the early days of photography in Finland (1839-1870) is characterised by a restricted and simplified picture form, the central feature of which is rigorism, i.e. the severe rigidity that occurs in all photographs of the age. Photography of the period is therefore referred to in this thesis by the term the severe age. The severe age lasted in its strict form as the hard period up until the early part of the 1850's. This was followed up until the middle of the 1850's by the soft period, which was the result of technical advances in photography. The great style of early photography appeared at the beginning of the 1860's, and is called vignettism in this study. Vignettism is the gradual disappearance of the edges of the face, background and surroundings of the subject by means of a light effect. It is the first stylistic revolution in photography. Photography in its modem sense did not appear until the 1870's, when the exposure time was reduced so, much that a snapped photograph could be taken that captured unstudied features in the picture. An analysis of the origin of photomontage in the 1860's and of collage round about 1870 is still important from the point of view of art history.